Priority-based SenCar deployment strategy for mobile sink data gathering in WSN. Issue 3 (3rd October 2022) - Patil, Sunita S.; Kumaran, T. Senthil
Data gathering using mobile sinks introduces new challenges to wireless sensor network (WSN) applications. Most of the approaches use single mobile sink or data collector which may not cover the entire network in time. The SenCars with multiple antennas select the optimum pair of sensor nodes to gather data simultaneously. In this paper, a priority based SenCar deployment strategy (PSDS) for mobile sink data gathering is proposed. In this scheme, the priority of sensed data determined depending on the urgency and deadline of data. Then one SenCar is deployed for collecting high priority (critical data) by directly visiting to the respective sensors. Another SenCar is deployed for collecting the low priority (non-critical data) from other sensors. Simulation results have shown that the proposed PSDS scheme achieves better PDR and higher residual energy with minimum data gathering delay.